Celebration of the Prophet Muhammad’s Birthday (Mawlid Nabi) by Muslim Community in Canberra - Hadi, Abd.; Lalu Dodi Suwandi; Alvinatun; Lutfifah Septiyatin; Nila Khairatul Muslimah; Winda Ayu Setia Ningrum; Riadatul Isnawati (Ta’dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2024)
This essay observes the ceremony of the Prophet Muhammad’s birthday celebration on the 12th of Rabi’ al-Awwal 1409 Hijrah in Canberra by Indonesian Muslim community. Considering the congregational nature of the mawlid celebration I will employ the functionalist approach of Durkheim in analysing the celebration of the mawlid as religious ritual and a communal experience rather than an individual one. Through this perspective I wish to answer the question: What is the mawlid celebration serves (as a function) for Indonesian Muslim community in Canberra? In addition, I also utilize Geertz’s perspective in theorizing religion as a cultural system that consists of a worldview and ethos. As such, mawlid ceremony as one of the most commonly held festival by Muslim communities all over the world provides spaces for revitalizing and strengthening Islamic identity (particularly for Muslim diasporas) and as a religious observance for spiritual rejuvenation by presenting the prophet Muhammad as a role model for all Muslims.